US–China External Imbalance and the Global Financial Crisis - Lin, Justin Yifu; Dinh, Hinh T.; Im, Fernando (Taylor and Francis, 2013)
This paper advances an alternative explanation of the large external imbalance between the United States and China, and its linkages to the current global financial crisis. We show that US current account deficits dated back long before the emergence of China's recent large trade surpluses, with China accounting at its peak for at most one-third of this deficit. The relative rise in China's savings in recent years can be attributed to an increase in its corporate savings, a trend that reflects distortions arising from the transition process from a planned to a market economy. These distortions exacerbate China's income inequality, causing domestic consumption to remain a small share of GDP. Large recent current account deficits in the United States, on the other hand, can be attributed to public sector disserving and perverse incentives generated by housing and equity bubbles, made possible by loose monetary policy and by “innovative” financial derivatives arising from the financial deregulation in the early 1980s. The paper shows that short-run measures are unlikely to fully address these external imbalances. Both countries require long-run, structural measures to resolve the underlying problems and to restore a sustainable foundation for growth.